Transformation in the work of small agricultural producers in the context of the digitalization of agriculture - Ximenes, Elvia Florencio Torres; Montedo, Uiara Bandineli; Pinto, Liliane Araújo (Seven Editora, 2023)
Rapid and radical changes have been experienced by many workers, so the article aimed to discuss the new paradigms of work in the face of changes brought about by digitalization and, subsequently, the ways that this has affected the daily life of workers in agriculture. To achieve the objective, a literature review was carried out along with articles from the Scopus and Google Scholar platforms. The results reveal issues that bring up needs that have never been felt before, but which are incorporated into everyday life, making human beings dependent on technologies to address such needs in practically all areas of life. DOI: https://doi.org/10.56238/devopinterscie-053